2016
DOI: 10.1186/s13046-016-0396-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of claudin-6 promotes breast cancer cell migration and invasion by recruiting MeCP2 and deacetylating H3Ac and H4Ac

Abstract: BackgroundClaudin-6 (CLDN6), a member of claudin transmembrane protein family, has recently been reported to be undetectable or at low levels in human breast cancer cell lines and tissues and plays a role in suppression of migration and invasion in breast cancer cells. In addition, it is reported that CLDN6 expression is regulated by DNA methylation in various human cancers and cell lines. However, it is unclear how DNA methylation regulates CLDN6 expression. Here we show the mechanism by which DNA methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 34 publications
(35 reference statements)
2
50
0
Order By: Relevance
“…DNA methylation is a key regulatory mechanism in normal development and disease pathways for several diseases, including cancer (Tsaprouni et al 2014, Zhang et al 2016. Alterations in DNA methylation status have been reported to regulate chromatin structure, and potentially influence transcription (Sneller and Gunter 1987, Kang et al 2015, Liu et al 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is a key regulatory mechanism in normal development and disease pathways for several diseases, including cancer (Tsaprouni et al 2014, Zhang et al 2016. Alterations in DNA methylation status have been reported to regulate chromatin structure, and potentially influence transcription (Sneller and Gunter 1987, Kang et al 2015, Liu et al 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 So far, there are limited data available on claudin (CLDN), epigenetics, and the relation to claudin protein expression as well as its role in the development of colorectal carcinoma (CRC). While DNA methylation of claudin 6 has been shown to be involved in the invasion of breast cancer cells 3 Abstract Altered claudin expression has been described in colon, prostatic, ovarian, and breast carcinoma. However, the role of epigenetic modifications in these genes and their role in colorectal cancer is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing MECP2 reduces human prostate transformed cell proliferation [31]. Recent research has found that MECP2 regulates cancer cell migration and invasion in glioma and breast cancer [32,33]. Our previous studies have proved that MECP2 promotes cell proliferation and cell cycle G1-S transition, and restrains cell apoptosis in liver cancer, gastric cancer and breast cancer [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%